THRIVING AS A HYBRID MEDIUM: A PHILIPPINE COMMUNITY RADIO EXPERIENCE - Annabelle B. Francisco (Universitas PGRI Madiun, 2022)
This work investigated in-depth the structure, management and leadership, human resources, programming and program content, participation and funding of an award winning hybrid community radio in the Philippines which has succeeded to adopt and adapt to digitalization. The shift from the traditional analogue medium to digital is a major transformation for community radio stations in general. The blending was not made instantly. The change was taken one day at a time backed up by empirical data. With the decision to go digital, Radyo Kailian as community radios today and in the years to come therefore, are faced with bigger expectations, responsibilities, and commitments. As a hybrid medium, Radyo Kailian as a CRS is: expected to produce on air and online programs which are acceptable to the standards of its glocal stakeholders; responsible in ensuring that digital tools are utilized essentially, effectively, and creatively; and remain committed to retain it community radio identity despite the alteration in its mode of delivery